2017
DOI: 10.1149/2.1201712jes
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Modeling of Chemical Membrane Degradation and Mitigation in Ceria-Supported Fuel Cells

Abstract: Ceria-supported membrane electrode assemblies (MEAs) have recently been proposed to address chemical membrane degradation in polymer electrolyte fuel cells. Although ceria is known to effectively protect the membrane at open circuit voltage (OCV) conditions, its effectiveness has not been demonstrated for cell voltages below OCV and associated conditions relevant for field operation. In the present work, a comprehensive, transient in situ chemical degradation model for ceria stabilized MEAs is developed and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 49 publications
3
40
0
2
Order By: Relevance
“…Simulations show that more than 99% of the cerium ions reside in the trivalent state and hence, are active for quenching OH, the most destructive oxygen species. This is well in line with the modelling results by Gubler et al 101 and Wong and Kjeang, 45,103 who also found that the dominant oxidation state in the cerium system is +III.…”
Section: Mitigation Of Fuel Cell Degradation With Cerium Saltssupporting
confidence: 92%
See 4 more Smart Citations
“…Simulations show that more than 99% of the cerium ions reside in the trivalent state and hence, are active for quenching OH, the most destructive oxygen species. This is well in line with the modelling results by Gubler et al 101 and Wong and Kjeang, 45,103 who also found that the dominant oxidation state in the cerium system is +III.…”
Section: Mitigation Of Fuel Cell Degradation With Cerium Saltssupporting
confidence: 92%
“…When ceria is incorporated into the membrane, it dissolves under operating conditions and produces both trivalent and tetravalent cerium ions. 45,99 A detailed scheme describing how CeO 2 mitigates membrane degradation by scavenging ROS was presented by Prabhakaran et al 47 The most stable oxidation states +III and +IV form a redox couple (E 0 (Ce 3+ /Ce 4+ ) = À1.44 V Fig. 13 The calculated fluoride emission rate (averaged over 100 h) is plotted as function of t 99 .…”
Section: Mitigation Of Fuel Cell Degradation With Cerium Saltsmentioning
confidence: 99%
See 3 more Smart Citations